Organellar protein multi-functionality and phenotypic plasticity in plants. (20th January 2020) - Mackenzie, Sally A.; Kundariya, Hardik
Abstract : With the increasing impact of climate instability on agricultural and ecological systems has come a heightened sense of urgency to understand plant adaptation mechanisms in more detail. Plant species have a remarkable ability to disperse their progeny to a wide range of environments, demonstrating extraordinary resiliency mechanisms that incorporate epigenetics and transgenerational stability. Surprisingly, some of the underlying versatility of plants to adapt to abiotic and biotic stress emerges from the neofunctionalization of organelles and organellar proteins. We describe evidence of possible plastid specialization and multi-functional organellar protein features that serve to enhance plant phenotypic plasticity. These features appear to rely on, for example, spatio-temporal regulation of plastid composition, and unusual interorganellar protein targeting and retrograde signalling features that facilitate multi-functionalization. Although we report in detail on three such specializations, involving MSH1, WHIRLY1 and CUE1 proteins in Arabidopsis, there is ample reason to believe that these represent only a fraction of what is yet to be discovered as we begin to elaborate cross-species diversity. Recent observations suggest that plant proteins previously defined in one context may soon be rediscovered in new roles and that much more detailed investigation of proteins that show subcellular multi-targeting may be warranted. This article is part of the theme issue 'Linking the mitochondrial genotype to phenotype: a complex endeavour'.